Genetic characterization and lineage analysis of Pasundan (Rancah) cattle in West Java, Indonesia: Insights from ZFY gene sequencing - Arifin, Johar; Bayu Putra, Widya Pintaka; Said, Syahruddin; Tyasi, Thobela Louis (Livestock and Animal Research, 2023)
Objective: This study was carried out to characterize Pasundan (Rancah) cattle from West Java of Indonesia based on a partial Zinc Finger Y-linked (ZFY) gene sequence.Methods: Total of fourteen (14) DNA samples of unrelated Pasundan bulls at the breeding station (BPPIBT-SP Ciamis, West Java) were used for sequencing analysis. The blood samples were collected from jugular vein of each bull for the DNA extraction analysis. Along 979 bp of ZFY gene was amplified using primer pairs of forward: 5’- GGT GAG GGC ACA TGA GTT C -3’and reverse:  5’- CTC TGC AGG TGG TTG TGT AA -3’. Therefore, a forward sequencing method was performed in the present study to obtain the ZFY gene sequences. Along 714 bp of bovine ZFY gene sequences were used for determining the Neighbor-Joining (NJ) tree for Pasundan bulls with 1000 × bootstrap replications using a MEGA computer program. The genetic diversity parameters of haplotype diversity (Hd), nucleotide diversity (pi), Tajima’s D test and Fu’s Fs statistics were calculated using a DNAsp computer program.Results: Total of fourteen (14) haplotypes of ZFY gene and seventy (70) mutation sites were detected in the Pasundan bulls. The haplotype diversity (Hd) and nucleotide diversity (pi) in Pasundan’s ZFY gene diversity were 1.00 (high) and 0.01 (low), respectively. The neutrality test of Tajima’s D and Fu’s Fs statistic values were -1.42 and -6.47, respectively. Bovine ZFY gene can be classified into two clades of ZFY-1 and ZFY-2. Therefore, the Neighbor-joining (NJ) tree (1000×bootstrap) revealed that the Pasundan cattle are classified into clade ZFY-1 together with Bos taurus (AF241273, AF465179). Meanwhile, a clade ZFY-2 consisted of Bos taurus (AF465181, DQ336536), Bos indicus (DQ336537), and Bos javanicus (DQ336578).Conclusion: The ZFY gene of Pasundan bulls were polymorphic with seventy mutation sites. Therefore, Pasundan bulls were characterized into ZFY-1 clade or Taurine lineage based on ZFY gene sequence variaton. The crossbreeding program with Bos taurus straw to increase meat production of cattle may affecting the genetic structure of Pasundan bulls since this program is widely applied in West Java through many years ago.